Cooption and Repression in the Soviet Union - Grossman, Hershel (IMF Working Papers; Working Paper, 2000)
The Soviet ruling elite, the nomenklatura, used both cooption and political repression to encourage loyalty to the communist regime. Loyalty was critical both in defusing internal opposition to the rule of the nomenklatura and in either deterring or defeating foreign enemies of the Soviet Union. We assume that the nomenklatura determined the extent of cooption and the intensity of political repression by equating their perceived marginal benefits and marginal costs. We use this assumption to construct an account of the historical evolution of policies of cooption and political repression in the Soviet Union.